Cyto-SAT: A self-assessment tool for the safe handling of cytotoxic drugs adapted for use in low- and middle-income countries. (August 2021) - von Grünigen, Sandrine; Geissbühler, Antoine; Bonnabry, Pascal
Introduction: The handling of cytotoxic medicines is a high-risk process for human and environmental health. Considering the rising burden of cancer in low- and middle-income countries (LMICs), we aimed to develop, validate, and pilot test a self-assessment tool to support the implementation of safe handling practices and promote continuous quality improvement for cytotoxic drug management in LMICs. Methods: First, the self-assessment tool Cyto-SAT was developed and validated. Key sources on the safe handling of cytotoxic medicines were reviewed to derive items addressing safety and quality aspects at every stage of the process. A two-round online Delphi survey was conducted to validate and prioritize the items. The validation rules in the first and second rounds were defined as ≥65% and ≥75% agreement, respectively. Then, intended users in healthcare facilities in LMICs evaluated the Cyto-SAT tool in a pilot test. They were asked to fill out an online evaluation questionnaire. Results: Twenty-seven experts from 13 high-income countries and LMICs participated in the Delphi survey. Final expert consensus was achieved for 134/137 (97.8%) items. Consensus on priority was achieved for 52 of 134 (38.8%) items. The final Cyto-SAT tool comprises 134 items in 10 domains and 28 subdomains covering the whole cytotoxic drug handling process (https://pharmed.datapharma.ch/cyto-sat_en/ ). Staff from 34 institutions in 28 LMICs completed the Cyto-SAT evaluation. Almost all of them reported total agreement or agreement with its usefulness (96%), applicability (94%), usability (98%), and acceptability (97%). Conclusion: Cyto-SAT is the first self-assessment tool designed to assist professionals in LMICs in the safe handling of cytotoxic drugs. The pilot test revealed that Cyto-SAT is a useful and highly appreciated tool that supports practice improvement in LMICs. Cyto-SAT will be used in an international survey to obtain a global overview of handling practices in various LMIC settings.